Структурні характеристики соціалізації економіки України: визначення та динаміка змін - Вишневський, О.С. (Управління економікою: теорія та практика, 2013)
Визначено структурні характеристики соціалізації економіки України. Переважна більшість цих характеристик має негативну динаміку, що свідчить про десоціалізацію економіки України. Для поглиблення соціалізації економіки України запропоновано напрями структурних маневрів. Определены структурные характеристики социализации экономики Украины. Подавляющее большинство этих характеристик имеет отрицательную динамику, что свидетельствует о десоциализации экономики Украины. Для углубления социализации экономики Украины предложены направления структурных маневров. The purpose of this article is to determine the structural characteristics of the socialization of the economy of Ukraine and assess the dynamics of their changes. The current state and trends in the structural characteristics of the socialization of the economy indicates the presence of countervailing trends with the dominant negative. From 17 structural indicators, only 6 have a positive trend, 10 - negative trend, 1 figure - mixed trend. Significant structural problems occur in the social orientation of production, where among the structural parameters of 5 from 6 have negative trend and only 1 has positive trend . The most notable deterioration occurs with innovative products. Their share in the industrial output in Ukraine has decreased twofold from 2007 to 2012. The low share of innovative products to some extent is due to the low proportion of machine building in the manufacturing industry, which equal only 11.1% as of 2012 that is less by 2-3 times than in the economically developed countries of the EU. Positive changes occurred only in respect of education of people employed in the industry, where the share of persons with an incom plete education, with college and higher education has increased during 2008-2012 years on 4 pp. Thus, the socialization of production primarily calls for structural maneuvers aimed at enhancing innovative products by expanding high-tech industries and attracting highly qualified personnel. Positive trends in the provision of socially oriented distribution and redistribution relate to the increases in social spending and increase in the share of labor costs in GDP. At the same time, the tax policy indicates the desocialization of distribution goods and services. Value added tax is replacing profit tax. This indicates changing sources of financing public expenditure from people who have economic success, toward the totality of the population.The increase in final consumption expenditure in GDP and decrease in household expenditures on food are positive features areas of social orientated consumption of goods and services. This decrease in the share of services in GDP realized by the population indicates a desocialization of consumption. So, general trends in socialization of consumption of goods and services are positive. Environment for social orientation of the economy is poor and requires structural changes towards increasing the share of human capital in the structure of national wealth and increasing the share of the population that sees positive economic developments in the country and identify themselves as the driving force of these processes.